Shifting routines among families with school-age children with disabilities due to mandatory school closures during the COVID-19 pandemic in Québec, Canada - Giordano, Gustina; Kathol, Katja; Flanagan, Tara (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2023)
This study explored the changes in routine and the social and emotional impacts experienced by families of children with parent-reported learning differences or disabilities (“disabilities”) due to mandatory school closures during COVID-19 in Québec, Canada. A questionnaire was used to compare the family routines of 20 participants before and after the school closures. The study’s findings highlight an overall concern regarding outcomes of long-term school closures. Family routines after the school closures included increased technology usage, decreased socialization, a cease or decline of extracurriculars and therapies, and an increase in symptoms of depression and anxiety among this cohort. The authors suggest enhanced support services, including psychosocial services and financial aid, to mitigate potential negative outcomes.